Above-ground arthropod community structure and influence of structural-retention management in southern Patagonian scrublands, Argentina - Sola, Francisco Javier; Peri, Pablo Luis; Huertas, Laura Eugenia; Martínez Pastur, Guillermo José; Lencinas, María Vanessa (Springer, 2018)
Southern Patagonia’s landscape hosts several semi-natural habitats, traditionally used for sheep production, such as Mulguraea tridens and Lepidophyllum cupressiforme scrublands. Mulguraea scrublands are managed via mechanical shredding to remove shrubs and increase grass availability, alternating with structural-retention strips. We analyzed the influence of structural-retention management (with cut and retention strips) in Mulguraea scrublands with regards to above-ground arthropod community structure, as well as differences between the two natural scrubland types. We worked in Santa Cruz Province (Argentina) with pitfall traps during two summers in the first 2 years after mechanical shredding. Richness, abundance, occurrence frequency, Shannon–Wiener diversity and Pielou evenness indices, and similarity among assemblages were evaluated using univariate and multivariate statistical tests. Complementarily, we described vegetation ground cover and microclimate. We collected 3279 individuals from 38 species belonging to Insecta and Arachnida Classes. Shannon–Wiener diversity and Pielou evenness indices, as well as the overall assemblages, differed significantly between managed cut strips and natural Mulguraea scrublands, mainly due to the loss and introduction of species from surrounding environments; abundance also differed in the first sampling year compared to the second year. Likewise, managed retention strips allowed the partial maintenance of arthropod community structure and had a microclimate that was similar to natural Mulguraea scrublands, although assemblages in managed cut and retention strips became more similar among themselves in the second sampling year. On the other hand, richness, abundance and assemblage of both natural scrubland types differed significantly, with 87 % more indicator species in Mulguraea than in Lepidophyllum scrublands. Greater dissimilarity occurred between both natural scrubland types in dryer years, which could be related with an El Niño Southern Oscillation event. If arthropod community structure changes prove stable over time, mechanical shredding with structural-retention management would allow for an increase in the sheep carrying capacity, while reducing impacts to the arthropod community, thus providing a viable compromise between productivity and conservation in a fragile arid environment. More studies are necessary to evaluate long term changes in above-ground arthropod community structure of scrublands in arid zones of southern Patagonia.